2022
DOI: 10.3390/ijerph19148514
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impacts of Urban Community Leisure on Subjective Well-Being during COVID-19: A Mixed Methods Case Study

Abstract: Participating in community leisure activities has become an important way for the public to pursue good health and a high quality of life. However, few studies have focused on the health and welfare effects of participating in urban leisure activities during the COVID-19 pandemic. In response to this gap in the literature, this study drew on the stimulus–organism–response (SOR) theory to examine the effects of community leisure on subjective well-being during the pandemic from the perspective of urban resident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…Ref. [76] associates it with an individual's ability to engage in activities aligned with their values. The OECD adopts this dimension as flourishing or the development of an individual's potential.…”
Section: Eudaimoniamentioning
confidence: 99%
“…Ref. [76] associates it with an individual's ability to engage in activities aligned with their values. The OECD adopts this dimension as flourishing or the development of an individual's potential.…”
Section: Eudaimoniamentioning
confidence: 99%
“…Factors influencing S-O-R include lighting, temperature, noise levels, air quality, and natural elements such as plants and water (Kim et al, 2020). Understanding S-O-R is vital for creating comfortable and healthy environments conducive to productivity and well-being (Wang et al, 2022). This concept is particularly relevant in the design of green buildings and hotels, prioritizing the sustainability and well-being of guests and the environment.…”
Section: Stimulus-organism-response (S-o-r)mentioning
confidence: 99%
“…The fifth attribute is leisure expenditure. Scholars have claimed that leisure activity relieves stress and makes individuals happier as it enables them to escape from tedious daily life [ 48 , 49 , 50 , 51 ]. Noll and Weick [ 16 ] have also shown that subjective health in Germany is positively influenced by expenditure on leisure.…”
Section: Review Of Literature and Hypotheses Developmentmentioning
confidence: 99%